Journalistic innovation: How new formats of digital journalism are perceived in the academic literature. (April 2023) - Lopezosa, Carlos; Codina, Lluís; Fernández-Planells, Ariadna; Freixa, Pere
This article carries out a systematic review of the literature analysing the following new journalistic formats: structured journalism, immersive journalism, 360° video reports, virtual reality and augmented reality applied to journalism, newsgames and docugames. To do so, the scientific production examining these formats is first analysed to determine the academic impact of these studies, while identifying their characteristics and tracking their evolution over time. Second, the leading researchers in this field are identified and interviewed to ascertain their opinion about the future of journalism and changing trends in journalistic formats. The results show that the number of academic publications about journalistic innovation peaked in 2019, above all in the three journals – Digital Journalism, Journalism Practice and Profesional de la Información – that lead the way in this discipline. The 23 academics interviewed reported that innovation impacts primarily on four aspects of journalism: information and content; audience; methods and resources and news media companies.